Mitchell, Taylor & Talbot on confiscation and the proceeds of crime - Mitchell, Andrew R. (Sweet & Maxwell LondonGB, 2004)
Sets out the law relating to confiscation and the proceeds of crime in the form in which it was before the Proceeds of Crime Act 2002 and the law following the introduction of the Act.